Visioning and backcasting on transport and the environment - Banister, D (Nagoya University International Research Center for Sustainable Transport and Cities, 2009)
Paper presented at WCTRS SIG11 Transport and the Environment and NU-SUSTRAC International Symposium 13-14 November 2009 Nagoya on Transport and Climate Change.